Spatial distribution of estuarine diamond-backed terrapins (Malaclemys terrapin) and risk analysis from commercial blue crab (Callinectes sapidus) trapping at the Savannah Coastal Refuges Complex, USA. (1st May 2018) - Lovich, Jeffrey E.; Thomas, Meagan; Ironside, Kirsten; Yackulic, Charles; Puffer, Shellie R.
Abstract: The diamond-backed terrapin ( Malaclemys terrapin ) is a small estuarine turtle distributed along the Atlantic and Gulf Coasts of the USA. Terrapin populations are declining throughout their range and one of the main causes is mortality by drowning as bycatch in commercially-fished blue crab ( Callinectes sapidus ) traps (aka pots). We conducted head counts of terrapins and documented the distribution and number of crab pots on the Savannah Coastal Refuges Complex in southeast Georgia, USA. Using an index for representing relative degree of crabbing pressure, we conducted a spatial risk analysis for each of the four refuges surveyed. We fit a series of generalized linear mixed effect models to test hypotheses about the scale (creek scale vs. refuge/island scale) at which terrapin relative abundances respond to crab trapping and environmental variables. Several creeks were found to be at high risk of terrapin mortality from crab pots. Areas with low terrapin head counts may be a result of past crab pot mortality. The best model relating terrapin counts to crab trapping revealed a negative effect of crab pots calculated at the refuge/island scale and included a positive association between cloud cover and terrapin counts. The estimated effect of crab pot number at the refuge/island scale suggests that an increase in crab pot density of one pot per creek is associated with a 74.6% decline in terrapin head counts, underscoring the sensitivity of terrapin populations to crab pot mortality. Mitigation of this mortality factor via redesigned crab traps with bycatch reduction devices may be necessary to maintain healthy terrapin populations on the refuges. Highlights: Terrapin detection is negatively related to crab trap density at a landscape scale. Increasing crab traps by one per creek results in a 74.6% decline terrapin detection. Bycatch reduction devices can reduce terrapin mortality.